Exciton–Ligand Interactions in PbS Quantum Dots Capped with Metal Chalcogenides - Papagiorgis, Paris; Tsokkou, Demetra; Kushagra, Gahlot; Protesescu, Loredana; Manoli, Andreas; Hermerschmidt, Felix; Christodoulou, Constantinos; Choulis, Stelios A.; Kovalenko, Maksym V.; Othonos, Andreas S.; Itskos, Grigorios (My University, 2020)
Colloidal quantum dots (CQDs) are typically decorated with organic molecules that provide surface passivation and colloidal solubility. An alternate but less studied surface functionalization approach via inorganic complexes can produce stable CQDs with attractive transport and optical properties. Further development of such all-inorganic CQD solids is dependent on the deeper understanding of the energetic and dynamic interactions of the new ligands with the CQD excitons. Herein, a series of four metal chalcogenide (MCC) ligands of the KzXS4 type were attached to PbS CQDs. Out of the four MCC complexes studied, we find that only K4GeS4 ligands yield robust PbS CQD films with bright photoluminescence (PL) in the solid state. A systematic spectroscopic investigation of the K4GeS4-capped CQD films provides evidence of the temperature-dependent ligand-mediated exciton delocalization and trapping processes. At low temperatures, efficient trapping at ligand-induced states is found to occur within ∼6 ns after photoexcitation, followed by a considerably slower exciton back transfer to the CQD core. At elevated temperatures, the CQD films become photoconductive, providing evidence of exciton dissociation via carrier transfer within adjacent dots. The addition of a thin CdS shell suppresses the delocalization and trapping of excitons, resulting in brighter emission and significantly slower transient absorption and PL dynamics.
Keywords: Colloidal quantum dots; Surface passivation; Colloidal solubility; Spectroscopic investigation